Brucellosis control methods with an emphasis on vaccination: a systematic review. Issue 7 (3rd July 2022) - Darbandi, Atieh; Koupaei, Maryam; Navidifar, Tahereh; Shahroodian, Soheila; Heidary, Mohsen; Talebi, Malihe
ABSTRACT: Introduction: Brucellosis is considered as one of the main zoonotic infections and a major public health concern worldwide. The aim of the present study was to evaluate various strategies for controlling brucellosis with an especial emphasis on efficacy of vaccination. Areas covered: International databanks (Web of Science, PubMed, Embase) were searched for potentially relevant studies published from 1 January 2011 to 25 March 2021 using the following keywords: ' Brucella, ' ' Brucella abortus, ' ' Brucella melitensis, ' ' Brucella canis, ' ' Brucella suis, ' 'brucellosis, ' 'Bang disease, ' 'undulant fever, ' 'Malta fever, ' 'vaccination, ' 'vaccine, ' and 'immunization.' The literature search was restricted to original articles published in English. Expert opinion: Various methods are employed to prevent and control brucellosis, such as removing sick animals by slaughtering, separating sick animals from the herd, and vaccination. Preventing, controlling, and eradicating brucellosis requires a lot of financial support, perseverance, and time. In order to conduct a detailed study, it is recommended that more studies be conducted in developing countries and different parts of the world.